The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1980
DOI: 10.1039/p29800001391
|View full text |Cite
|
Sign up to set email alerts
|

The thermal ring opening of 3,3-disubstituted cyclobutenes

Abstract: The rates of the thermal unimolecular isomerisation of 3-t-butyl-3-methylcyclobutene and 3-methyl-3-phenylcyclobutene have been measured in the gas phase over the temperature ranges 158-190' and 120-180", respectively. They are correlated by the Arrhenius expressions k = 1 014-08 * o*80exp( -1 50.8 f 2.5/RT) sand k = 1 012.60 * O*lzexp( -1 26.1 5 f 0.95/RT) s-l, respectively. The ratio of Z-to €-isomer of the butadienes formed has been measured both for these two and for the 3-methyl-3-R-cyclobutenes, where R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…The olefination of ketones via ynolates corresponds to the ring-opening of 3,3-dialkyl(or aryl)cyclobutenes, which was extensively studied by Stevens 20 and Houk. 25 Stevens reported that 3-tert-butyl-3-methylcyclobutenes preferentially gave the E-isomer as the major isomer, which is not in accord with our results (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…The olefination of ketones via ynolates corresponds to the ring-opening of 3,3-dialkyl(or aryl)cyclobutenes, which was extensively studied by Stevens 20 and Houk. 25 Stevens reported that 3-tert-butyl-3-methylcyclobutenes preferentially gave the E-isomer as the major isomer, which is not in accord with our results (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…In this investigation, therefore, we select five ring‐opening reactions where the Frontier molecular orbital (FMO) theory has not been satisfactory (see R1 and R2‐R5 ) in explaining the reaction mechanism; 3‐methyl‐cyclobut‐1‐ene ( R1) , 3‐(ethyl, methyl)‐cyclobut‐1‐ene ( R2 ), 3‐(isopropyl, methyl)‐cyclobut‐1‐ene ( R3 ), 3‐(terbutyl,methyl)‐cyclobut‐1‐ene ( R4 ), and 3‐(phenyl, methyl)‐cyclobut‐1‐ene ( R5 ), see Scheme and Table . We choose a series of reactions R1 ‐ R5 with contrasting nuclear skeletons and activation energies, conventionally considered to be either competitive or noncompetitive on the basis of Δ TS < 1.0 kcal/mol, see Scheme , Table , and Figure .…”
Section: Introductionmentioning
confidence: 99%
“…The cut‐off for stereospecificity is defined to be for experiment yields of approximately 70% for R1 and for R2‐R5, the dominant product is displayed for clarity in a bold font.…”
Section: Introductionmentioning
confidence: 99%
“…Curry and Stevens published a systematic study of the stereochemistry of ring-opening of 3,3-disubstituted cyclobutenes in 1980, and in interpreting their surprising results, they made the first attempt to rationalize the stereochemistry of the ring-opening process in terms other than steric effects. However, the full demise of the steric rationale did not occur until the papers of Dolbier, Burton, Koroniak, et al and Houk, Rondan, and Kirmse appeared in 1984, wherein it became crystal clear that electronic effects , not steric effects, were dominant in determining both the kinetic and the stereochemical behavior of 3-substituted cyclobutenes.…”
mentioning
confidence: 99%